Exploring synergies between India's climate change and land degradation targets: Lessons from the Glasgow Climate COP. (20th October 2022) - Dhyani, Shalini; Santhanam, Harini; Dasgupta, Rajarshi; Bhaskar, Dhanya; Murthy, Indu K.; Singh, Kripal
Abstract: Land degradation, extending over 96 million hectares is a primary ecological issue for India that has resulted in catastrophic biodiversity loss and exacerbated extreme weather occurrences. One of the major sources of land degradation is large‐scale coal mining to realize country's expanding energy demands. By 2050 climate change and land degradation, will result in US$1730 billion loss for India. Climate COP in Glasgow, 2021 was a watershed event to confront broader climate change challenges. India made one of the boldest pledges to pursue the road of climate justice, protect the most vulnerable, and committed to achieving net‐zero emissions by 2070. This means gradually phasing down coal, reducing emissions and mainstreaming renewable sources. Given the prospect of five challenging but attainable targets, we examine India's readiness and the ramifications of these targets on land degradation reduction. Indian government is continuously increasing strategic support for improved mine closure and mine void restoration while, ensuring that land restoration supports 'green' job creation for poverty alleviation. While there is focus on investing significant amounts of national funding to address land degradation, international and private finances can enable to accomplish the larger goals. To enhance the effectiveness of the promises, we propose embedding diverse knowledge systems including indigenous knowledge systems and capabilities by formulating policies that incentivize environmental restoration, people‐centric, climate sensitive strategies, convergence between different government departments as well as schemes, and mainstreaming of systems thinking as a social transformation approach for achieving coupled Climate and Land Degradation Neutrality targets by 2030 and 2070.